Acute toxicity study of d-trans allethrin and d-phenothrin to zebrafish, danio rerio and its human relevance - Abd Hamid, Abdul Alif; Md Isa, Muhammad Lokman; Lee, Siew Pien; Nik Hassan, Nik Fakhuruddin; Muhammad, Hussin; Harmili, - (Media Shed, 2024)
In Malaysia, insecticide spray is widely used in a household environment, and most consumers are not aware of its exposure effects. As evidence by reported insecticide intoxication cases involving hospitalisation and fatality cases suggested insufficient studies on insecticide usage and its exposure effects. Commonly insecticide constitutes of type 1 pyrethroids with allethrin and d-phenothrin featured prominently in most insecticide products. Hence, the acute toxicity study of allethrin and d-phenothrin mixture which represents the insecticide consumer product was conducted to provide data on insecticide consumer product toxicological information. Adult zebrafish were randomly selected and exposed to the insecticide mixture. The clinical sign of toxicosis and mortality rate of the zebrafish were observed in 96 h period. The toxicosis characteristics of the zebrafish during the study were documented and interpreted using the OECD TG203 and the mortalities were computed and analysed using statistical package SPSS version 26. Based on the LC50 obtained the HED and MTD were calculated. The insecticide-exposed zebrafish exhibits changes in their locomotion and respiration. The LC50 values for d-trans allethrin and d-phenothrin were 0.80 and 0.51 μg/L with HED were 0.003 and 0.002 μg /kg and the MTD were 0.18 and 0.12 μg /kg respectively. The finding indicates insecticide toxicity effects were observed in the zebrafish model. Considering the toxicity effects, levels, insecticide required and extrapolated MTD data, there is a legitimate risk exposure for humans when these substances were extensively used daily in the home environment.